International Comparison of High-Technology Manufacturing and Knowledge-Intensive Services in the EU - Auziņa-Emsiņa, Astra (Economics and Business, 2015)
High-technology industries that apply the most advanced and cutting edge technologies are frequently analysed as an opposite to low-technology industries. Following a similar approach, services are subdivided by knowledge-intensity into two major dichotomic groups: knowledge-intensive services and less knowledge-intensive services. The aim of the research is to evaluate how these industries perform in reality, whether these industries have the largest value added and highest efficiency and productivity level as it is believed by theory and various policy documents.